2021
DOI: 10.1371/journal.pone.0247856
|View full text |Cite
|
Sign up to set email alerts
|

The double burden of malnutrition in India: Trends and inequalities (2006–2016)

Abstract: Rapid urban expansion has important health implications. This study examines trends and inequalities in undernutrition and overnutrition by gender, residence (rural, urban slum, urban non-slum), and wealth among children and adults in India. We used National Family Health Survey data from 2006 and 2016 (n = 311,182 children 0-5y and 972,192 adults 15-54y in total). We calculated differences, slope index of inequality (SII) and concentration index to examine changes over time and inequalities in outcomes by gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 27 publications
5
38
2
Order By: Relevance
“…Recently the Government of India also launched the National Nutrition Strategy (in 2017) and the National Nutrition Mission (in 2018). The National Nutrition Mission provides an updated strategic framework for action to improve nutritional outcomes by holistically addressing the multiple determinants of malnutrition, through cross-sectoral convergence and contextualized planning at each level of the implementation process [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently the Government of India also launched the National Nutrition Strategy (in 2017) and the National Nutrition Mission (in 2018). The National Nutrition Mission provides an updated strategic framework for action to improve nutritional outcomes by holistically addressing the multiple determinants of malnutrition, through cross-sectoral convergence and contextualized planning at each level of the implementation process [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…An imbalance between the macro and micronutrients required for metabolism reactions leads to malnutrition. One of its forms is undernutrition resulting from nutrient deficiencies (these terms are often incorrectly used interchangeably) [1]. Unfortunately, elemental deficiencies are still a relevant health issue in developing and underdeveloped countries [2].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that obesity is identified as an independent risk factor for COVID-19 disease severity and obese children may experience a more severe COVID-19 trajectory which might include the need for respiratory support. 7 The overall obesity of 53.01% was high as compared to pre-covid era estimations of 19.3% 8 and ~7-8%, 9 respectively.…”
Section: Discussionmentioning
confidence: 82%